Tense Relationships between Homicide Co-Victims and Detectives in the Wake of Murder. Issue 5 (3rd May 2020) - Reed, Mark D.; Dabney, Dean A.; Tapp, Susannah Naomi; Ishoy, Glen A.
ABSTRACT: In the aftermath of a murder, homicide detectives and the loved ones of slain victims have no choice but to interact with one another over a lengthy period of time. These relationships are among the most mutually unwelcome and emotionally challenging that beset the criminal justice system. Drawing upon interviews with homicide detectives and homicide co-victims, the purpose of this study is to examine the patterned aspects of these relationships as they unfold across three predictable phases of the postmortem process: at the crime scene, during the death notification, and throughout the follow up investigation. We document distinct themes to how both groups perceive the stress and trauma that they experience across each phase of the relationship. In doing so, we seek to theorize a largely underappreciated aspect of the criminal justice process and provide direction for policy makers.